Effective suppression of HIV-1 replication by cytotoxic T lymphocytes specific for pol epitopes in conserved mosaic vaccine immunogens - Zou, C; Murakoshi, H; Kuse, N; Akahoshi, T; Chikata, T; Gatanaga, H; Oka, S; Hanke, T; Takiguchi, M (American Society for Microbiology, 2019)
Cytotoxic T lymphocytes (CTLs) with strong abilities to suppress HIV-1 replication and recognize circulating HIV-1 could be key for both HIV-1 cure and prophylaxis. We recently designed conserved mosaic T-cell vaccine immunogens tHIVconsvX composed of 6 Gag and Pol regions. Since the tHIVconsvX vaccine targets conserved regions common to most global HIV-1 variants and employs a bi-valent mosaic design, it is expected that it could be universal if the vaccine works. Although we recently demonstrated that CTLs specific for 5 Gag epitopes in the vaccine immunogens had strong ability to suppress HIV-1 replication in vitro and in vivo, it remains unknown whether or not the Pol region-specific CTLs are equally efficient. Here, we studied CTLs specific for Pol epitopes in the immunogens in treatment-naïve Japanese patients infected with HIV-1 clade B. Overall, we mapped 20 reported and 5 novel Pol conserved epitopes in tHIVconsvX. Responses to 6 Pol epitopes were significantly associated with good clinical outcome, suggesting that CTLs specific for these 6 Pol epitopes had a strong ability to suppress HIV-1 replication in HIV-1-infected individuals. In vitro T-cell analyses further confirmed that the Pol-specific CTLs could effectively suppress HIV-1 replication. The present study thus demonstrated that the Pol regions of the vaccine contained protective epitopes. T-cell responses to the previous 5 Gag and present 6 Pol protective epitopes together also showed a strong correlation with better clinical outcome. These findings support the testing of the conserved mosaic vaccine in HIV-1 cure and prevention in humans. IMPORTANCE It is likely necessary for an effective AIDS vaccine to elicit CD8+ T cells with the ability to recognize circulating HIV-1 and suppress their replication. We recently developed novel bivalent-mosaic T-cell vaccine immunogens composed of conserved regions of the Gag and Pol proteins match to at least 80% globally circulating HIV-1 isolates. Nevertheless, it remains to be proven if vaccine with these immunogens can elicit T cells with the ability to suppress HIV-1 replication. It is well known that Gag-specific T cells can suppress HIV-1 replication more effectively than T cells specific for epitopes in other proteins. We recently identified 5 protective Gag epitopes in the vaccine immunogens. We here identified T cells specific for 6 Pol epitopes present in the immunogens with strong abilities to suppress HIV-1 in vivo and in vitro. This study further encourages clinical testing of the conserved mosaic T-cell vaccine in HIV-1 prevention and cure.